The relationship between early maladaptive schema, psychopathic traits, and neuroticism in an offender sample. (14th May 2015) - Daffern, Michael; Gilbert, Flora; Lee, Stuart; Chu, Chi Meng
Abstract: Background: Psychopathy is a complex and controversial diagnosis of significant clinical and forensic interest. However, little is known about how individuals with psychopathy interpret and construct their interpersonal environment. This is of critical importance to our understanding of psychopathy and the development of psychological treatments. The aim of this study was to explore the relationship between early maladaptive schema (EMS), neuroticism, and psychopathic traits in an offender sample. Methods: Sixty‐eight offenders participating in pre‐sentence psychiatric and/or psychological intervention completed psychological tests measuring EMS, neuroticism, and psychopathy. Results: Consistent with theorising and empirical evidence supporting the presence of different types of psychopathy, the profile of EMS in this sample was significantly different for participants with higher levels of neuroticism. Participants with higher levels of neuroticism had higher scores on the following EMS: abandonment, mistrust/abuse, emotional deprivation, practical incompetence, vulnerability to harm, failure to achieve, insufficient self‐control, subjugation, pessimism/worry, emotional inhibition, and defectiveness/unlovability. Conclusions: Higher neuroticism, irrespective of severity of psychopathic traits, is associated with a broad range of dysfunctional and pervasive beliefs about oneself and others. Abstract :